Yersinia molecular and cellular biology - Carniel, Elisabeth (Horizon bioscience, 2004)
Horizon Scientific Press titles focus on high-level microbiology and molecular biology topics. Written by internationally renowned and highly respected leaders in the field, they comprise review manuals, practical manuals, and reference texts for research scientists, bioscience professionals and graduate students. Yersinia strains are important human pathogens causing diseases ranging from the deadly Plague (Yersinia pestis) to a relatively mild gastroenteritis (e.g. Y. enterocolitica and Y. pseudotuberculosis). Plague is currently classed as a re-emerging disease that is endemic in many parts of the world. Since Y. pestis is highly lethal (a very small number of bacilli are enough to kill someone in a matter of days) it could be used by bioterrorists as a formidable airborne adversary. This has provided the impetus for a renewed interest in Yersinia molecular and cellular biology. Written by the top Yersinia specialists, the book reviews the molecular biology of these important organisms and comprehensively covers recent advances in the field. Topics include genetic diversity in Y. pestis, quorum sensing, identification of virulence genes, regulation of virulence elements, superantigens, host invasion, host immune response, LPS structure and genetics, flagellar-dependent motility, flagellar-dependent protein secretion, iron or heme transport systems, Yersinia pathogenicity Islands, the Yop effector proteins, plasminogen activator (Pla), F1 antigen, and the conjugative plasmid pVM82. Essential reading for everyone with an interest in Yersinia and recommended reading for other scientists with an interest in, for example, bioterrorism, microbial pathogenesis, microbial genomics, and antimicrobials.